Analysis of Studies of the Distribution of Input Disturbances of Potato Harvesting Machines and Evaluation of Moment Functionals in a Competing Risk Model using an Empirical Bayesian Approach (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2025)
This article studies the input disturbances of potato harvesting machines, i.e. separation of potato tubers from the mass and estimation of moment functionals in a competing risks model using an empirical Bayesian approach. The process of separation of soil from potatoes at the elevator of a potato harvester, which is exposed to competing risks, is considered as an elementary event. Here, the studied non-negative random variable (r.v.) means the stable operation of the tested technical device under consideration.